Modeling Forest Stand Dynamics, Growth and Yield - Harold E. Burkhart (MDPI AG, 2021)
The world’s forests are diverse and serve myriad purposes; however, regardless of the management objective, reliable models of forest stand dynamics, growth and yield are required [...]